Expressive writing changes grief into meaning – a sequential explanatory design approach - Savitri, Setiawati Intan; Takwin, Bagus; Ariyanto, Amarina Ashar; Aribowo, Rachel T.A (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2019)
The purpose of the present study was to describe the effect of expressive writing on the level of one’s grief through a sequential design (expressive writing experiments for 3 consecutive days for 15 minutes each days then an analysis of the participant’s writing contents was conducted). This study used a pre-post test matching technique experimental design follow up by content analysis. The total number of participants (both in the experimental and control groups) was 30 (M-age = 21.2; SD = 1.2), lost their parents more than six month. Randomized matching technique was use to divide participant into experimental (expressive writing) and control (non-expressive writing).The baseline score measured by the complicated grieving inventory of >25 (Prigereson, 1995). Results showed that the experimental group had a decreased level of grief relative to the control group, the texts showed an interested result to be further discussed.